The Relation Of The International Accounting Standard Ias2 For Stock On Environmental Costs - Sidali ,Somia; Maida ,Mohamed Faycel (جامعة الوادي University of Eloued, 2024)
This study seeks to elucidate the concept of inventories and their significance in accordance with the Standard Financial Accounting (SCF) and several international accounting standards, including International Accounting Standard 2 (IAS 2). The study examines the evaluation and classification of inventories and their influence on the financial performance of organizations. The paper examines the significance of environmental costs and their integration into inventory expenses to promote sustainable growth. The study encompasses an examination of the various facets of sustainable development and its objectives, along with offering recommendations to enhance openness and accountability in financial and environmental reporting
The relation of The International Accounting Standard IAS2 for Stock on environmental costs and support for sustainable development
Keywords: Sustainable Development; Environmental Costs; Stock; International Accounting Standard IAS2.